Historical Analysis of Wind Turbine Fire Incidents - Adriana Palacios; Erika Palacios-Rosas; Tawfiq Abdulaziz-Almughanam; Carolina Sohn-Favela; Jose De Jesus Gonzalez-Jimenez (Chemical Engineering Transactions)
Fires in wind turbines represent a critical issue in the renewable energy industry, as they result in significant economic losses and pose considerable risks to public health and the environment. Given the global growth in wind farm installations, fire prevention and management have become an increasingly relevant challenge. To better understand this issue, a database has been created, compiling 478 wind turbine fire incidents that occurred between 2000 and 2024. This historical analysis includes information on the date and location of the incidents, technical characteristics of the affected turbines, and the turbine manufacturers involved. The reported fires have been recorded across various regions, mainly in the Americas and Europe. On average, 20 fires have been reported annually, although various studies suggest that the actual number is much higher. This study provides valuable insights for decision-makers in the wind energy sector, aiming to improve safety regulations and reduce the occurrence of fires in the fut